2013
DOI: 10.1016/j.etap.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene modulates fluoranthene-induced cellular responses in HT-29 colon cells in a dual exposure system

Abstract: Our environment is contaminated with a diverse array of chemicals; one of which is polycyclic aromatic hydrocarbons (PAHs). While some PAHs are potent by nature, others undergo interactions such as additivity, synergism, antagonism or potentiation to manifest their toxicity. Therefore, the objective of this study was to investigate whether exposure to benzo(a)pyrene (BaP), a PAH compound influences the cytotoxicity and metabolism of fluoranthene (FLA; another PAH compound) using HT-29 cells. Cells cultured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Similar effects on CYP-mediated metabolism were observed in vivo in male Sprague-Dawley rats exposed to binary PAH mixtures (Bouchard et al 1998) and increased DNA adduct levels have been observed in vitro in hamster embryo cells exposed to a mixture of B[a]P and benzo[e]pyrene (Smolarek and Baird 1984). A recent in vitro study in human-derived colorectal adenocarcinoma (HT-29) cells observed dose-dependent increased fluoranthene metabolism after co-exposure with B[a]P which the authors attributed to enhanced CYP-mediated activation of fluoranthene, although neither gene expression or CYP activity was measured directly (Harris et al 2013).…”
Section: Effects Of Interactions In Binary Pah Mixturesmentioning
confidence: 99%
“…Similar effects on CYP-mediated metabolism were observed in vivo in male Sprague-Dawley rats exposed to binary PAH mixtures (Bouchard et al 1998) and increased DNA adduct levels have been observed in vitro in hamster embryo cells exposed to a mixture of B[a]P and benzo[e]pyrene (Smolarek and Baird 1984). A recent in vitro study in human-derived colorectal adenocarcinoma (HT-29) cells observed dose-dependent increased fluoranthene metabolism after co-exposure with B[a]P which the authors attributed to enhanced CYP-mediated activation of fluoranthene, although neither gene expression or CYP activity was measured directly (Harris et al 2013).…”
Section: Effects Of Interactions In Binary Pah Mixturesmentioning
confidence: 99%
“…The severity of toxicity is dependent on the combination of PAHs present in the mixture, their relative proportions and how they are metabolized. Polycyclic aromatic hydrocarbon-induced carcinogenesis requires long term exposure to an individual PAH compound [[30], [31], [32]] or mixtures [33]. This issue brings to light the strong interactions between various PAHs and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the exposure time in the in vitro experiments is limited, the relative higher doses were used in this study. Besides our study, similar doses have been used in other in vitro experiment (Tampio et al, 2008;Tampio et al, 2009;Harris et al, 2013;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%